Proceedings of the 4th International Conference on Numerical Modelling in Engineering Volume 1: Numerical modelling in Civil Engineering, NME 2021, 24-25 August, Ghent University, Belgium - Wahab, Magd Abdel; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book gathers outstanding papers on numerical modeling in Civil Engineering (Volume 1) as part of the 2-volume proceedings of the 4th International Conference on Numerical Modeling in Engineering (NME 2021), which was held in Ghent, Belgium, on 24-25 August 2021. The overall objective of the conference was to bring together international scientists and engineers in academia and industry from fields related to advanced numerical techniques, such as the finite element method (FEM), boundary element method (BEM), isogeometric analysis (IGA), etc., and their applications to a wide range of engineering disciplines. This volume covers numerical simulations with industrial civil engineering applications such as bridges and dams, cyclic loading, fluid dynamics, structural mechanics, geotechnical engineering, thermal analysis, reinforced concrete structures, steel structures, and composite structures.
Structural mechanics -- Fluid dynamics -- Geotechnical engineering -- Thermal analysis.
Keywords: Civil engineering; Numerical analysis; Mathematical physics; Civil Engineering; Numerical Analysis; Theoretical, Mathematical and Computational Physics; Engineering -- Mathematical models -- Congresses